2018
DOI: 10.1016/j.vetpar.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Safety and serologic response to a Haemonchus contortus vaccine in alpacas

Abstract: Haemonchosis in camelids remains a challenging disease to treat, and prevention has become increasingly problematic due to widespread anthelmintic resistance. Barbervaxis an adjuvanted vaccine containing natural H-11, H-gal-GP antigens obtained from Haemonchus contortus adults via a proprietary process and solubilized in Quil A. This vaccine is approved for use in Australia, after demonstrating its safety and efficacy in sheep and goats. There are no published studies evaluating Barbervax in other ruminants/ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Administration of rHcADRM1 antigen elicited sufficient levels of immune protection in H. contortus-inoculated goats, resulting in 48.9 and 58.6% reductions in cumulative FEC and worm burden, respectively. As demonstrated by the protective mechanism of action for Barbervax (LeJambre et al, 2008;VanHoy et al, 2018), the levels of repeated immunizations-induced antigenspecific antibodies (mainly IgG) were well correlated with the protective efficacy of an anti-H. contortus vaccine. Hence, anti-rHcADRM1 IgG was employed in the parallel passive trial and was shown to confer encouraging levels of protection to inoculated goats by reducing cumulative FEC and worm burden by 46.7 and 56.2%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Administration of rHcADRM1 antigen elicited sufficient levels of immune protection in H. contortus-inoculated goats, resulting in 48.9 and 58.6% reductions in cumulative FEC and worm burden, respectively. As demonstrated by the protective mechanism of action for Barbervax (LeJambre et al, 2008;VanHoy et al, 2018), the levels of repeated immunizations-induced antigenspecific antibodies (mainly IgG) were well correlated with the protective efficacy of an anti-H. contortus vaccine. Hence, anti-rHcADRM1 IgG was employed in the parallel passive trial and was shown to confer encouraging levels of protection to inoculated goats by reducing cumulative FEC and worm burden by 46.7 and 56.2%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Both antigens may induce strong protective immunity in sheep and goats when used separately. Vaccine trials of Barbervax ® have confirmed elevated serum immunoglobulin levels and significant reductions of faecal egg count and worm burden in vaccinated animals [ 40 , 59 , 84 , 85 , 86 ]. Currently, native H11 and H-gal-GP antigens have to be isolated from H. contortus adults derived from the abomasa of donor sheep upon slaughter, since adult parasites cannot be obtained by in vitro cultivation.…”
Section: Vaccination Against H Contortusmentioning
confidence: 99%
“…A vaccine named Barbervax® has been recently licensed to be marketed in Australia which contain two native integral gut membrane protein H11 and H-gal-GP from H. controtus (Nisbet et al 2016). During evaluation of safety and serological outcome of this vaccine significant antibody titers have been detected in the vaccinated animals (Vanhoy et al 2018).…”
Section: Importancementioning
confidence: 99%